2002
DOI: 10.1103/physrevb.66.035409
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of the surface-growth kinetics of reducedTiO2(110)during reoxidation using time-resolved scanning tunneling microscopy

Abstract: We have employed variable-temperature scanning tunneling microscopy ͑STM͒ to follow the kinetics of reoxidation of a nonstoichiometric TiO 2 ͑110͒ single-crystal surface. The surface is seen to grow during reoxidation between 573 and 1000 K and at pressures from 5ϫ10 Ϫ8 to 2ϫ10 Ϫ6 mbar O 2 . The reaction proceeds by combination of gas-phase O 2 with mobile interstitial Ti 3ϩ from the bulk. The surface is observed to grow new layers of TiO 2 in a cyclic process, resulting in the formation of alternate layers of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
39
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 29 publications
8
39
0
Order By: Relevance
“…Whilst our finding that Ti interstitials are more energetically favourable than adatoms agrees with experimental results for adatoms diffusing down into the bulk upon annealing, 14 trapping them in the bulk by such a large amount as 2.5 eV does not accord with the re-growth of reduced rutile at elevated temperature, even if oxygen ad-species promote the growth. 9,10,15 We conclude that the empirical QEq potential of Hallil et al 28 overestimates the adsorption energy of the interstitials with respect to the adatom energy.…”
Section: The Structure and Energy Of Interstitials In The (110) Surfacementioning
confidence: 68%
“…Whilst our finding that Ti interstitials are more energetically favourable than adatoms agrees with experimental results for adatoms diffusing down into the bulk upon annealing, 14 trapping them in the bulk by such a large amount as 2.5 eV does not accord with the re-growth of reduced rutile at elevated temperature, even if oxygen ad-species promote the growth. 9,10,15 We conclude that the empirical QEq potential of Hallil et al 28 overestimates the adsorption energy of the interstitials with respect to the adatom energy.…”
Section: The Structure and Energy Of Interstitials In The (110) Surfacementioning
confidence: 68%
“…11,12 The observations showed that the rutile ͑110͒ surface grows by combination of gas-phase oxygen with mobile interstitial Ti 3+ ions from the bulk. The diffusion and reaction of titanium interstitials with adsorbed oxygen have been examined theoretically, 13 and it was found that the energy barriers for Ti interstitial diffusion and reaction were 0.75 and 1.2 eV, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…This titanium-covered surface is then oxidised by molecular oxygen and further TiCl 4 can adsorb and decompose. Bowker and co-workers investigated the kinetics of the reoxidation of reduced TiO 2 {110} [9], however, the full cycle of the growth is not yet fully understood. A scheme of the presumed surface growth from layer n to layer n+1 is given in Figure 1.…”
Section: Introductionmentioning
confidence: 99%